Спеціально-кримінологічні заходи запобігання невиконанню судових рішень - Лагода, К. О.; Lahoda, K. O. (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 1 (68). - С. 71-80., 2015)
Досліджено спеціально-кримінологічні заходи запобігання невиконанню судового рішення. Акцентовано увагу на необхідності усунення криміногенних прогалин у правовому регулюванні строків виконання судових рішень, порядку виконання судових рішень у справах, у яких боржником є держава. Окремо досліджено можливості удосконалення кримінально-правових заходів запобігання невиконанню судових рішень. Надано розгорнуту характеристику кожному з цих заходів.

Special attention is paid to such special and criminological measures of preventing non-compliance with judicial decisions as: 1) elimination of criminogenic gaps in the legal regulation of terms of executing judicial decisions; 2) improving legal regulation of the procedure of executing judgments in cases, where the debtor is the state, namely: a) strengthening of legal guarantees of the state on its obligations according to the decisions of national courts; b) fixing an exhaustive list of grounds for denial of funds to a creditor according to the judgment in situations, where the manager of such funds is the Ministry of Justice of Ukraine; c) to eliminate corrupt implications of the law that may be factors for non-compliance with judicial decisions, introduction of the amendments offered by the author to the Law of Ukraine «On state guarantees of executing judicial decisions»; 3) improvement of the mechanism of legal regulation of executing judgments of the Constitutional Court of Ukraine and adoption of the Law of Ukraine «On the procedure of executing judgments of the Constitutional Court of Ukraine»; 4) improving penal measures to prevent non-compliance with judicial decisions by abandoning the prejudicial nature of the features of the objective side of corpus delicti under the Art. 382 of the Criminal Code of Ukraine. The author proves that non-compliance with judicial decisions and inhibition of their execution on the one hand and non-performance of the state executing officer’s decisions – on the other finds parallel coexistence of two distinct kinds of antisocial (criminal) practices. The first infringes on relations of justice, the second – on the authority of public authorities. Therefore, it is offered and grounded to amend the Law of Ukraine «On executory proceedings».

Исследованы специально-криминологические меры предупреждения неисполнения судебных решений. Акцентировано внимание на необходимости устранения криминогенных пробелов в правовом регулировании сроков исполнения судебных решений, порядка исполнения судебных решений в делах, по которым должником является государство. Отдельно исследованы возможности совершенствования уголовно-правовых мер предупреждения неисполнения судебных решений. Дана развернутая характеристика каждой из этих мер.
Lahoda, K.O. (2015), “Special and criminological measures to prevent non-compliance with judicial decisions” [“Spetsialo-kryminolohichni zakhody zapobihannia nevykonanniu sudovykh rishen”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 1, pp. 71-80.
Лагода, К. О. Спеціально-кримінологічні заходи запобігання невиконанню судових рішень // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 1 (68). - С. 71-80.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Кримінологія. Criminology. Криминология; судове рішення; judgment; судебное решение; невиконання судового рішення; запобігання; правове регулювання; кримінально-правовий захист; non-compliance with a judicial decision; prevention; legal regulation; criminal and legal protection; неисполнение судебного решения; предупреждение; правовое регулирование; уголовно-правовая защита